Predictors of sexual satisfaction among patients with chronic pain - Barr, Aex; Moore, Kayla; Flegge, Lindsay G.; Atsaphanthong, Emily; Kirby, Krissa E.; Craner, Julia R. (Frontiers in Pain Research, 2024)
Objectives Sexual satisfaction is an important aspect of quality of life. Chronic pain, depression and anxiety, and relational problems correspond with higher risk for sexual difficulties. Less is known about how risk factors for sexual dysfunction and other problems—such as medical conditions, pain severity, and medication side effects—affect the sexual satisfaction of people with chronic pain. Using a biopsychosocial framework, this study explored factors related to sexual satisfaction among patients presenting for evaluation of chronic pain. Methods Researchers used a hierarchical multiple regression analysis to model potential predictors of sexual satisfaction. Variables analyzed were demographic features, medical history, average pain severity, depressed mood, anxiety, and perceived significant other support. Data collection involved administration of retrospective questionnaires and chart review. The sample included male and female participants (N = 134) presenting for evaluation at a multidisciplinary pain rehabilitation clinic. Results Medical history (i.e., medical conditions, surgical history, and medications) and clinical self-report variables (i.e., pain severity, depressed mood, anxiety, and perceived significant other support) were associated with sexual satisfaction. In this sample, antidepressant use and higher pain severity were unique predictors of lower sexual satisfaction. Married marital status and higher levels of perceived significant other support were predictive of greater sexual satisfaction. Discussion Findings highlight the importance of understanding the unique impact of biopsychosocial variables on the sexual satisfaction of patients presenting for evaluation at a multidisciplinary pain rehabilitation clinic. Further exploration of protective factors that account for sexual satisfaction among individuals with chronic pain may help inform screening, referrals, and treatment.